A Laterally Extended Perylene Hexacarboxylate via Diels-Alder Reaction for High-Performance Organic Lithium-Ion Batteries. (10th November 2017) - Li, Lei; Hong, Yu-Jian; Chen, Dong-Yang; Lin, Mei-Jin
Graphical abstract: The lateral extension of the well-known tetralithium perylene tetracarboxylate leads to perylene hexacarboxylate (Li6 -BPHC, see TOC) via a facile Diels-Alder reaction, which possesses an enhanced performance for organic lithium-ion batteries. Highlights: Diels-Alder reaction is an efficient strategy to incorporate more redox groups into and extend π systems in one-step. Diels-Alder reaction is anticipated to be an efficient approach to achieve high-performance organic electrode materials. A laterally extended perylene hexacarboxylate via Diels-Alder reaction has been design as a proof-of-concept example. The electrochemical studies indicated it indeed possess a higher specific capacity and more stable cycling performance. This finding is of considerable realistic significance for the high-performance organic electrode materials. Abstract: The Diels-Alder reaction is a well-known [4 + 2] cycloaddition in organic chemistry, which is employed in this article as an efficient approach towards high-performance organic electrode materials since it can achieve the incorporation of more redox groups and extension of π systems in one step. As a proof-of-concept example, we reported that a hexalithium benzo[ghi]perylene hexacarboxylate (Li6 -BPHC) by the lateral extension of well-known organic anode material, tetralithium perylene tetracarboxylate (Li4 -PTC), via a facile Diels-Alder reaction, which has been demonstrated to not only store nearly six electrons per molecule at a current density of 280 mA g −1 but also possess a highly stable cycling performance over 100 cycles.